Indonesian National Army Involvement in Handling Terrorism Action from Legal Perspective - Wilma Silalahi (Fakultas Hukum Universitas Lampung, 2021)
The crime of terrorism is an extraordinary crime against humanity, including a “serious crime” whose number of actions has increased. It requires handling with exceptional measures and